Epigallocathechin-3 Gallate Selectively Inhibits the PDGF-BB–induced Intracellular Signaling Transduction Pathway in Vascular Smooth Muscle Cells and Inhibits Transformation of sis-transfected NIH 3T3 Fibroblasts and Human Glioblastoma Cells (A172) - Ahn, Hee-Yul (The American Society for Cell Biology, 1999)
Enhanced activity of receptor tyrosine kinases such as the PDGF β-receptor and EGF receptor has been implicated as a contributing factor in the development of malignant and nonmalignant proliferative diseases such as cancer and atherosclerosis. Several epidemiological studies suggest that green tea may prevent the development of cancer and atherosclerosis. One of the major constituents of green tea is the polyphenol epigallocathechin-3 gallate (EGCG). In an attempt to offer a possible explanation for the anti-cancer and anti-atherosclerotic activity of EGCG, we examined the effect of EGCG on the PDGF-BB–, EGF-, angiotensin II-, and FCS-induced activation of the 44 kDa and 42 kDa mitogen-activated protein (MAP) kinase isoforms (p44(mapk)/p42(mapk)) in cultured vascular smooth muscle cells (VSMCs) from rat aorta. VSMCs were treated with EGCG (1–100 μM) for 24 h and stimulated with the above mentioned agonists for different time periods. Stimulation of the p44(mapk)/p42(mapk) was detected by the enhanced Western blotting method using phospho-specific MAP kinase antibodies that recognized the Tyr204-phosphorylated (active) isoforms. Treatment of VSMCs with 10 and 50 μM EGCG resulted in an 80% and a complete inhibition of the PDGF-BB–induced activation of MAP kinase isoforms, respectively. In striking contrast, EGCG (1–100 μM) did not influence MAP kinase activation by EGF, angiotensin II, and FCS. Similarly, the maximal effect of PDGF-BB on the c-fos and egr-1 mRNA expression as well as on intracellular free Ca(2+) concentration was completely inhibited in EGCG-treated VSMCs, whereas the effect of EGF was not affected. Quantification of the immunoprecipitated tyrosine-phosphorylated PDGF-Rβ, phosphatidylinositol 3′-kinase, and phospholipase C-γ1 by the enhanced Western blotting method revealed that EGCG treatment effectively inhibits tyrosine phosphorylation of these kinases in VSMCs. Furthermore, we show that spheroid formation of human glioblastoma cells (A172) and colony formation of sis-transfected NIH 3T3 cells in semisolid agar are completely inhibited by 20–50 μM EGCG. Our findings demonstrate that EGCG is a selective inhibitor of the tyrosine phosphorylation of PDGF-Rβ and its downstream signaling pathway. The present findings may partly explain the anti-cancer and anti-atherosclerotic activity of green tea.